Acoustofluidic Rotational Manipulation of Cells and Organisms Using Oscillating Solid Structures. Issue 37 (12th August 2016) - Ozcelik, Adem; Nama, Nitesh; Huang, Po‐Hsun; Kaynak, Murat; McReynolds, Melanie R.; Hanna‐Rose, Wendy; Huang, Tony Jun
Abstract : A polydimethylsiloxane microchannel featuring sidewall sharp‐edge structures and bare channels, and a piezoelement transducer is attached to a thin glass slide. When an external acoustic field is applied to the microchannel, the oscillation of the sharp‐edge structures and the thin glass slide generate acoustic streaming flows which in turn rotate single cells and C. elegans in‐plane and out‐of‐plane.